Isolation and Identification of Ananixanthone from Ethyl Acetate Extract of Root Bark Of Slatri (Calophyllum Soulattri) (Clusiaceae)) - Dindha Ramah Mulia; Nestri Wulandari; Muhammad Widyo Wartono (ALCHEMY Jurnal Penelitian Kimia, 2016)
A  xanthone,  named  ananixanthone  (1)  has  been  isolated  and  identified  from  the  ethyl acetate  extract of the root barks of  Calophyllum soulattri. Structure of the compound was determined based on spectroscopic data, including UV, IR, NMR 1D, NMR 2D and by comparison with references.